Estimation of Rice Productivity Using The Normalized Difference Vegetation Index (NDVI) Algorithm (Case Study of Gunung Talang District, Solok Regency) - Delvi Yanti; Khoirunnisa S; Rusnam; Eri Stiyanto (Jurnal Keteknikan Pertanian, 2022)
Rice productivity is closely related to rice harvested area and cropping intensity. Remote sensing technology using MODIS MOD13A1 v006 image produces Normalized Difference Vegetation Index (NDVI) values that can be interpreted in analyzing the value of rice productivity. Gunung Talang District has a rice field area of 3,369 m2, which is one of the central rice areas in West Sumatra Province. This study aimed to determine the regression equation to estimate rice productivity in Gunung Talang District, Solok Regency using the NDVI algorithm. The NDVI data used to generate the regression equation was taken in the generative phase. From the results of data analysis, the regression equation for estimating rice productivity in Talang District, Solok Regency is y = 250.33x4 - 1493.3x3 + 2293.6x2 - 1353.9x + 281.13, where x is the NDVI value and y is the productivity value (ton ha-1). The test results of the model's validity are expressed in the value of NSE (Nash-Sutcliffe Efficiency) is 0.66, which is categorized as adequate.